Application of environmental protection measures for clay loam Cambisol used for agricultural purposes - Arlauskienė, Aušra; Maikštėnienė, Stanislava; Šlepetienė, Alvyra (Journal of Environmental Engineering and Landscape Management, 2011)
Field experiments were done at the Joniškėlis Experimental Station of the Lithuanian Institute of Agriculture (LIA) during 2004–2006. The experiments were done on a productive clay loam Gleyic Cambisol used for agricultural production and were designed to estimate the effects of various catch crops—red clover (Trifolium pratense L.) and white clover (Trifolium repens L.) mixture with Italian ryegrass (Lolium multiflorumLamk.) and white mustard (Sinapis alba L.) biomass and wheat (Triticum aestivum L.) straw incorporated into the soil on the composition of humus. In the first year, incorporation of only catch crops biomass or together with straw increased the content of mobile humic acids (CHA1) by 10.7–28.0% compared with that before trial establishment. With increasing mobile humic acids content the contents of aggressive and free fulvic acids increased too (r = 0.80, p < 0.01; r = 0.85, p < 0.01, respectively). Conditionally stable humic acids fractions (CHA2, CHA3) formed more intensively in the second year of effects of the measures applied. The biomass of Fabaceae family plants incorporated alone or together with straw tended to increase the content of calcium-bound humic acids (CHA2). Having incorporated catch crops biomass together with straw, the fraction of humic acids CHA3 tended to increase or was the same as that before trial establishment. A slight reduction in the total amount of fulvic acids and an increase in the content of humic acids, compared with the levels before the trial establishment determined positive changes in the main indicators of humus quality—CHA : CFAratio and humification rate; they were the most distinct having incorporated red clover phytomass together with straw. Incorporation of mineral nitrogen fertilizer N45 together with straw increased soil organic matter mineralization rate and determined a reduction in humic acids content. Article in English. Aplinkosaugos priemonių taikymas agrarinés paskirties sunkaus priemolio rudžemiuose Santrauka. Lietuvos žemdirbystės instituto (LŽI) Joniškėlio bandymų stotyje 2004–2006 m. atlikti tyrimai, kurių tikslas buvo nustatyti našiame agrarinės paskirties sunkaus priemolio glėjiškame rudžemyje (Endocalcari-Endohypogleic Cambisol, CM-n-w-can) tarpiniuose pasėliuose augintų įvairių biologinių rūšių augalų – raudonųjų dobilų (Trifolium pratense L.), baltųjų dobilų (Trifolium repens L.) mišinio su gausiažiedėmis svidrėmis (Lolium multiflorum Lamk.) bei baltųjų garstyčių (Sinapis alba L.) biomasės ir paprastųjų kviečių (Triticum aestivum L.) šiaudų, įterptų į dirvožemį, įtaką humuso kokybei. Įterpus vien tarpiniųpasėlių biomasę ar kartu su šiaudais, pirmaisiais metais judriųjųhuminiųrūgščių (CHR1) kiekis, palyginti su buvusiu prieš bandymą, padidėjo 0,024–0,061 % C. Didėjant judriųjų huminių rūgščių kiekiui, didėjo ir agresyviųjų bei laisvųjų fulvinių rūgščių kiekis (atitinkamai r = 0,80, p > 0,01; r = 0,85, p > 0,01). Santykinai patvarios huminių rūgščių (CHR2, CHR3) frakcijos intensyviau formavosi antraisiais taikytų priemonių poveikio metais. Pupinių šeimos augalų biomasė, įterpta viena ar su šiaudais, didino huminių rūgščių junginio su kalciu (CHR2) kiekį. Įterpus tarpiniųpasėlių biomasę kartu su šiaudais, huminių rūgščių CHR3 frakcija tendencingai didėjo ar prilygo buvusiai prieš bandymą. Suminio fulvinių rūgščių kiekio nežymus sumažėjimas ir huminių rūgščių kiekio padidėjimas, palyginti su duomenimisprieš bandymą, lėmė teigiamus pagrindinių humuso kokybės rodiklių – CHR:CFR santykio ir humifikacijos laipsnio pokyčius; jie ryškiausi buvo į dirvožemį įterpus raudonųjų dobilų fitomasės kartu su šiaudais. Patręšus mineralinėmis azototrąšomis N45 kartu su šiaudais, didėjo dirvožemio organinių medžiagų mineralizacijos intensyvumas ir sumažėjo huminiųrūgščių. Reikšminiai žodžiai: glėjiškas rudžemis, tarpiniai pasėliai, šiaudai, huminės ir fulvinės rūgštys. Применение мер для охраны окружающей среды на тяжелосуглинистых буроземах аграрного назначения Резюме. В 2004–2006 гг. на Йонишкельской станции Литовского института земледелия (ЛИЗ) проводились исследования,целью которых было определить влияние биомассы выращиваемых в промежуточных посевах культур – клевера красного (Trifolium pratense L.), смеси клевера белого (Trifolium repens L.) и райграса однолетнего (Lolium multiflorum Lamk.), горчицы белой (Sinapis alba L.) и соломы пшеницы обыкновенной (Triticum aestivum L.) накачественный состав гумуса тяжелосуглинистого бурозема. Внесение в почву биомассы промежуточных культурили внесение их совместно с соломой пшеницы в первый год увеличило количество подвижных гуминовыхкислот (CГК1) на 10,7–28,0% по сравнению с их исходным количеством перед закладкой опыта. С увеличениемколичества подвижных CГК1 увеличивалось также количество фракций «агрессивных» и свободных фульвокислот (соответственно r = 0,80, p < 0,01; r = 0,85, p < 0,01).Относительно стабильные фракции гуминовых кислот (CГК2 иCГК3) интенсивнее формировались на второй год после действия исследуемых агротехнических приемов.Внесение биомассы бобовых культур в сочетании с соломой или без нее увеличило количество связанных скальцием гуминовых кислот (CГК2). При внесении биомассы промежуточных растений совместно с соломой формирование CГК3 увеличивалось и было аналогично их количеству перед закладкой опыта. Незначительноеснижение содержания в почве фульвокислот и увеличение количества гуминовых кислот, по сравнению сначальным уровнем до закладки опыта, определило положительные изменения основных показателей качествагумуса – соотношения CГК:CФК и степени гумификации. Более значительными они были при внесении фитомассыклевера красного совместно с соломой. Внесение минерального азота (N45) вместе с соломой увеличивалоинтенсивность минерализации органического вещества почвы и снижало количество гуминовых кислот. Ключевые слова: глееватый бурозем, промежуточные посевы, солома, гуминовые и фульвокислоты.